The Critical Role of Electron‐Donating Thiophene Groups on the Mechanical and Thermal Properties of Donor–Acceptor Semiconducting Polymers - Zhang, Song; Ocheje, Michael U.; Huang, Lifeng; Galuska, Luke; Cao, Zhiqiang; Luo, Shaochuan; Cheng, Yu‐Hsuan; Ehlenberg, Dakota; Goodman, Renée B.; Zhou, Dongshan; Liu, Yi; Chiu, Yu‐Cheng; et al. (Advanced electronic materials, 2019)
Organic semiconducting donor–acceptor polymers are promising candidates for stretchable electronics owing to their mechanical compliance. However, the effect of the electron‐donating thiophene group on the thermomechanical properties of conjugated polymers has not been carefully studied. Here, thin‐film mechanical properties are investigated for diketopyrrolopyrrole (DPP)‐based conjugated polymers with varying numbers of isolated thiophene moieties and sizes of fused thiophene rings in the polymer backbone. Interestingly, it is found that these thiophene units act as an antiplasticizer, where more isolated thiophene rings or bigger fused rings result in an increased glass transition temperature (Tg) of the polymer backbone, and consequently elastic modulus of the respective DPP polymers. Detailed morphological studies suggests that all samples show similar semicrystalline morphology. This antiplasticization effect also exists in para‐azaquinodimethane‐based conjugated polymers, indicating that this can be a general trend for various conjugated polymer systems. Using the knowledge gained above, a new DPP‐based polymer with increased alkyl side chain density through attaching alky chains to the thiophene unit is engineered. The new DPP polymer demonstrates a record low Tg, and 50% lower elastic modulus than a reference polymer without side‐chain decorated on the thiophene unit. This work provides a general design rule for making low‐Tg conjugated polymers for stretchable electronics. This paper investigates the effect of isolated/fused thiophene units on the thermomechanical properties of donor–acceptor conjugated polymers. In diketopyrrolopyrrole‐based polymers, it is observed that thiophene units in the main chain structure serve as the antiplasticizer, which increase the stiffness and glass transition temperature of polymer chains. This allows for the development of a much softer conjugated polymer.